2008
DOI: 10.19030/tlc.v5i2.1314
|View full text |Cite
|
Sign up to set email alerts
|

Using The Major Field Test-Business As An Assessment Tool And Impetus For Program Improvement: Fifteen Years Of Experience At Virginia Military Institute

Abstract: We examine the history of VMI's use of the Major Field Test as an assessment tool for its Department of Economics and Business. Further, we chronicle how the information gathered from a decade and a half of use has shaped the curriculum, faculty composition and policies within the Department. There is evidence that the policies surrounding how and when the Major Field Test is administered influences student performance on the test and that it can be a valuable component of a comprehensive assessment program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It also put a greater emphasis on critical thinking in course assignments by requiring students to explain their conclusions in the analysis of a situation, and it changed the curriculum by adding prerequisites and changing some courses from electives to required courses. Changes to required courses were also reported by the Virginia Military Institute (Bush, 2008), which also made faculty changes and policy changes to provide higher quality student learning. Changes to course content and student assignments were also reported in Ammons (2005), Hollister (2007, and Lawrence (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also put a greater emphasis on critical thinking in course assignments by requiring students to explain their conclusions in the analysis of a situation, and it changed the curriculum by adding prerequisites and changing some courses from electives to required courses. Changes to required courses were also reported by the Virginia Military Institute (Bush, 2008), which also made faculty changes and policy changes to provide higher quality student learning. Changes to course content and student assignments were also reported in Ammons (2005), Hollister (2007, and Lawrence (2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Score and nine Assessment Indicators associated with each of the previously described topical areas. While comparisons to scores from previously administered exams may be of interest, prior research has consistently shown that the primary way institutions interpret their performance is through a comparison of their institutional Mean Total Score to national averages (Bush, Duncan, Sexton, & West, 2008;McLaughlin & White, 2007;Wilson, 2008;Word & Rook, 2012). ETS enables these comparisons by providing data tables that supply scaled scores and percentiles for institutional means drawn directly from all administrations of the MFT-B during a focal period (2013b).…”
Section: Following Administration Of the Mft-b Ets Generates A Localmentioning
confidence: 99%
“…Consequently, use of these scores for AOL assessment requires detailed analysis of these characteristics. Bush, Duncan, Sexton, and West (2008) Allen and Bycio (1997) 176 57 GPA (business), SAT-V, SAT-M, Incentives GPA (high school, major, overall), Gender Bagamery, Lasik, and Nixon (2005) 169 45 GPA (preadmission), GPA (business core), SAT dummy, male (+)…”
Section: Determinants Of Student Performance On Mftb Scoresmentioning
confidence: 99%
“…Table 4 provides two examples that demonstrate how determinants of student performance can confound the use of MFTB scores for student learning assessment. It shows institutional MFTB percentile scores for the University of Arkansas, Fort Smith (Settlage & Settlage, 2011) and the Virginia Military Institute (Bush et al, 2008) for selected periods.…”
Section: Determinants Of Student Performance On Mftb Scoresmentioning
confidence: 99%
See 1 more Smart Citation